KINERJA PEMBANGUNAN KEPARIWISATAAN DI DESA KEBUN DURIAN KECAMATAN GUNUNG SAHILAN KABUPATEN KAMPAR - dailiati, surya; sudaryanto, sudaryanto (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2016)
President of the Republic of Indonesia Joko Widodo has targeted a number of foreign tourists in 2016reached 20 million to Indonesia. Various programs are being introduced to make it happen. This needs to besupported by local governments, including the Government of Kampar regency. Because in this district are one ofthe leading tourist attraction that is not managed well, but already well-known. Call it Durian Gardens, located inDistrict of Mount Sahilan Kampar, Riau. The purpose of this study is the first activity; to analyze the performanceof the tourism development Durian Gardens in Kampar regency. Second, to identify and analyze the barriers to thedevelopment of tourism in Kampar Regency Gardens Durian. The study was conducted in Desa Kebun Durian District of Mount Sahilan Kampar regency. Thepopulation in this study is the Government apparatus and related parties. Serve as the Village Head KeyInformance. The sampling technique used is the census for the government apparatus and techniques for publicaccidental. Sources and types of data in this study are primary and secondary. Data have been collected based onthe type and form of data, for subsequent qualitative data is analyzed descriptively.With the enactment of Law no.10/2009 About Tourism, the Tourism Development today Riau Indonesia in general and in particular shall refer tothe provisions of the Act. Tourism operations carried out by the principles as set out in Article 5 of the Law. DurianGardens development of tourism performance in Kampar regency unfavorable. Generally the respondentsanswered less well (14.75) and was quite good (14.25) while either (0).